Fundamental Factors and Islamic Stock Returns of Food and Beverage Companies in Indonesia - Amaroh, Siti; Zahro, Siti Mudrikatuz; Masturin, Masturin (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2020)
This study examines the influence of issuers’ fundamental factors on Islamic stock returns in Indonesia. It is documentary research with data from company financial reports in the food and beverage industry. The companies were listed on the Indonesia Sharia Stock Index during 2015-2019. The sample selection was based on purposive sampling. The selected companies continuously published financial statements and had no negative earning per share. Based on the inclusion criteria, nine consistent firms were entered in data processing by Eviews software through several stages. The first stage involved determining the panel data regression model with common, fixed, and random effect models. The second stage was the selection of the fit model using 3 tests, including Chow, Lagrangian Multiplier, and Classic Assumption. The common effect was the fit panel data regression model. The results show that Return on Assets positively influences Islamic stock returns. However, Debt to Equity Ratio and Earning per Share do not affect Islamic Stock returns. Therefore, investors should pay attention to ROA before investing in Islamic capital market.